STRATEGI PENGELOLAAN INDUSTRI ROTAN BERKELANJUTAN DI KOTA PEKANBARU - Gita Melisa Yolanda; Ridwan Manda Putra; Suwondo . (JURNAL ILMU-ILMU KEHUTANAN, 2023)
This study aims to determine the status of the sustainable management of the rattan industry in Pekanbaru City and to design a sustainable management strategy for the rattan industry. The types of data in this study are primary data and secondary data. Interview and observation data collection methods. The data analysis method in this research is multidimensional scaling (MDS). Sustainability was analyzed using MDS analysis with the help of the Rap-Insus Industry software. The status of the sustainable management of the rattan industry in Pekanbaru City in a multidimensional manner is in a fairly continuous category. The results of the analysis of each dimension are the ecological dimension (32.5%) the economic dimension (75.6%) the social dimension (54.3%) the technology dimension (36.1) and the partnership dimension (66.5%). The strategy for sustainable rattan industry management in Pekanbaru City is carried out by establishing policies in the production process (product quality standardization), processing of waste from industrial activities, and rules and policies in the use of raw materials.